PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI - Muhammad Ali (Master of Public Administration, Universitas Slamet Riyadi, 2017)
The aim of this research is to understand the influence of leadership style,included partisipative, delegative and style of democratic leadership on workmotivation in working field in Sekolah Tinggi Ilmu Sosial dan Ilmu PolitikAmal Ilmiah Yapis Wamena, either partially or simultantly. This research isanalysed by using descriptive correlational analysis method. The result ofthis research is partisipative, delegative and democratic leadership stylehave an effect on work motivation either partially or simultantly.Key words: Leadership Style, Work Motivation, Civil Servant